Lateral flow immunoassays combining enrichment and colorimetry-fluorescence quantitative detection of sulfamethazine in milk based on trifunctional magnetic nanobeads. (April 2019) - Fang, Bolong; Hu, Song; Wang, Chun; Yuan, Meifang; Huang, Zhen; Xing, Keyu; Liu, Daofeng; Peng, Juan; Lai, Weihua
Abstract: In this study, magnetic nanobeads (MNBs) were used as a trifunctional material in lateral flow immunoassay for quantitative detection of sulfamethazine (SM2 ) in milk. Magnetic enrichment aimed to reduce matrix effects. Naked-eye screening of SM2 was based on colorimetry of colored MNBs. The cut-off value of the naked-eye screening was 25 ng mL −1 . When the concentration of SM2 in the samples is equal to the cut-off value or higher, the lateral flow strips can be quantitatively detected via grayscale intensity based on colored MNBs. When the concentration of SM2 in the samples is less than the cut-off value, the lateral flow strips can be quantitatively detected by means of fluorescence intensity based on the fluorescence quenching effect of MNBs. Under optimal conditions, the linear range and limit of detection (LOD) of fluorescence lateral flow immunoassay were 0.033–33 ng mL −1 and 0.026 ng mL −1 respectively, while the linear range and LOD of colorimetric lateral flow immunoassay was 1–100 ng mL −1 and 0.71 ng mL −1, respectively. This novel method can be used for rapid and quantitative detection of SM2 in milk. Highlights: The trifunctional MNB-based LFIA was developed to detect SM2 . Colorimetry and fluorescence were used for two linear ranges, respectively. Samples could be screened firstly and then detected by colorimetry or fluorescence. LFIA reduced matrix effects, broadened linear range, and improved test sensitivity.